2020
DOI: 10.2147/dmso.s245096
|View full text |Cite
|
Sign up to set email alerts
|

<p>Relationship of Two-Hour Plasma Glucose and Abdominal Visceral Fat with Bone Mineral Density and Bone Mineral Content in Women with Different Glucose Metabolism Status</p>

Abstract: Background: Several studies have reported the relationship of diabetes mellitus (DM) and obesity with bone mineral density (BMD), but the conclusions remain unclear. This study aimed to provide more information for the relationship of plasma glucose and abdominal visceral fat (AVF) with BMD and bone mineral content (BMC) in women with different glucose metabolism status. Methods: Patients were screened by oral glucose tolerance test (OGTT) and were divided into three groups: normal glucose tolerance (NGT, n=13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…However, pathogenic fat depots, notably in the abdomen, have been hypothesized to contribute more to bone disability [15][16][17]. A recent study on more than 650000 adults showed that a rise in WC led to an obvious and rapid increase in fracture risk, independent of the body mass index (BMI) level (three groups: normal, overweight, and obese) [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, pathogenic fat depots, notably in the abdomen, have been hypothesized to contribute more to bone disability [15][16][17]. A recent study on more than 650000 adults showed that a rise in WC led to an obvious and rapid increase in fracture risk, independent of the body mass index (BMI) level (three groups: normal, overweight, and obese) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the BMD became higher. However, Jia et al [3] found in their study that BMD and BMC of the T2DM group were lower than those of the normal group. Our study suggested that blood sugar content and BMD of the lumbar spine had a curvilinear relationship.…”
Section: Discussionmentioning
confidence: 82%
“…Diabetes may cause a signi cant increase in the risk of osteoporosis, which has been proved [2].The BMD of T1DM patients decreases. However, the BMD of T2DM patients is usually normal and even becomes slightly higher [3][4][5]. The bone turnover of diabetes patients decreases and properties of bone materials and bone microstructure change.…”
Section: Introductionmentioning
confidence: 99%
“…Jia et al. found that 2-h plasma glucose negatively correlated with femoral neck aBMD and lumbar spine aBMD in women ( 20 ). However, the negative correlation was not observed in two studies about children ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%